Studies of Male Survivors of Myocardial Infarction due to “Essential” Atherosclerosis: II. Lipids and Lipoproteins - Little, J. Alick (1963)
Serum lipids (total, ester and free cholesterol, phospholipid and standard S(f) 0-12, 12-20, 20-100 and 100-400 lipoproteins) were determined in 102 men, ages 30-70, with atherosclerotic coronary heart disease (C.H.D.), free of hypertension, diabetes or other complicating variables. All the lipid fractions had a lognormal distribution. All were significantly higher than in the controls up to the seventh decade. An explanation for the declining serum lipid levels with age was found. Contrary to previous reports, there was no abnormality in the relation of various lipid fractions to one another in C.H.D. A spurious correlation between C/P ratio and total cholesterol was found in both groups. In separating coronary and control subjects, cholesterol and 0-12 lipoproteins were the most reliable criteria and were equal in this respect. The misclassification rises from 20% in the fourth to 33% in the seventh decade. C/P ratio offered no improvement. The triglyceride-containing 100-400 lipoprotein was an inferior discriminator. Employing all the lipid fractions, discriminant analysis provided a minimum 12% misclassification in the fourth decade. There was no demonstrable relationship of cholesterol to body measurements, physical activity or family history of C.H.D.